(untitled) (Bangladesh Journal of Botany, 2020)
Thermal properties of wild Castanea mollissima seeds embryos with different moisture contents, and the optimal moisture contents for cryopreservation were studied. Seeds of similar size and weight (3.5 ± 0.3g) were put in silica gel at 0 to 7 days, embryo moisture content, viability and thermal properties were measured everyday. The results showed that the onset temperature and the crystallization peak of the mean enthalpy decreased with the decrease of embryo moisture content. Exothermic peak disappeared when the seeds were dried for 4 days, with an embryo moisture content of 0.45 ± 0.15 gH2O/g dw. The unfrozen water content (WCu) was 0.247 gH2O/g dw. The optimal water content was found to be 0.45 ± 0.15 gH2O/g dw, with the survival of 76.2%. Castanea mollissima embryonic axes dehydration needs comprehensive consideration of exothermic peak, unfrozen water content, onset temperature and viability loss.